Molecular epidemiology of the 2022 monkeypox virus outbreak in Slovenia - Resman Rus, Katarina (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2023)
Introduction: Monkeypox virus (MPXV), typically endemic in West and Central Africa, has raised global concern due to the recent outbreak in several non-endemic countries with human-to-human transmission. Here we present a comprehensive analysis of MPXV genomes from Slovenia. Methods: Two real-time polymerase chain reaction (RT-PCR) assays for Orthopoxvirus (OPV) and MPXV genes were used for laboratory confirmation of mpox. Complete MPXV genomic sequences were obtained using nanopore long reads and Illumina technology. Phylogenetic analyses compared the Slovenian MPXV sequences with the global sequences. Results: A total of 49 laboratory-confirmed mpox cases were diagnosed in Slovenia in 2022, mainly affecting males under 40. In 48 cases, a complete genome sequence was obtained and phylogenetic analysis revealed five distinct lineages (B.1, B.1.14, B.1.2, B.1.3, and A.2.1), with B.1 and B.1.3 dominating, suggesting multiple introductions into Slovenia. Genome analysis revealed significant divergence from the reference MPXV-M5312_HM12_Rivers. Conclusions: The genetic diversity observed in the Slovenian MPXV sequences sheds light on the complex dynamics of the 2022 mpox outbreak and highlights the need for further research to understand the impact of mutations on MPXV functional characteristics and their role in the evolution and diversification of current lineages.
Keywords: B.1 lineage; filogenomska analiza; linija B.1; monkeypox virus; nadzor virusnega genoma; orthopoxvirus; ortopoksvirus; phylogenomic analysis; viral genome surveillance; virus opičjih koz